Development of a new type of elliptical/non-elliptical vibration coining approaches for manufacturing functional microstructure surfaces. (11th January 2019) - Wang, Rongqi; Zhou, Xiaoqin; Meng, Guangwei
Abstract: Taking its inspiration from traditional elliptical vibration cutting, this paper develops a type of elliptical/non-elliptical vibration coining (EVC/NEVC) for the cost-effective fabrication of functional microstructure surfaces that have a wide range of practical applications. Firstly, the toolpath generation and surface topography simulations of EVC processes are performed to numerically investigate the dependency of microstructure distribution on the main coining parameters. The traditional cutting toolpath with equal turning angle is replaced by a type of re-planned coining toolpath with equal arc length for the microstructure surfaces with uniform distribution. The undesired pile-up and sinking-in defects are revealed by using finite element analysis and plastic deformation theory. Secondly, the coupling analysis on assistant coining motion (ACM) and the matching analysis on assistant coining velocity (ACV) are conducted on EVC processes. A minimum distance, d s, is defined to determine whether the bad scratching damage induced by workpiece–indenter relative motions will occur on the EVC microstructure surfaces. On this basis, a novel type of perfect ACV curve is reconstructed, which can keep the workpiece–indenter relatively static throughout the entire period of contact deformation. Then a Fourier series expansion is adopted to accurately fit and practically substitute the reconstructed ACV curves, further regenerating an available non-harmonic ACM trajectory with definite integral operations. As a result, the new NEVC toolpath is re-planned to substitute the traditional EVC toolpath for higher forming accuracies. Finally, comparisons between the traditional EVC and innovative NEVC processes are performed through a series of coining experiments conducted on two different metallic materials. While the experimental results demonstrate the feasibility and effectiveness of both the EVC and NEVC processes in fabricating microstructure surfaces, the forming accuracy and processing flexibility of the proposed NEVC process is superior to that of the traditional EVC process.